Assessment of the effect of the reward policy for major grain-producing counties on county governments' incentives to support grain production - Ba, Xuezhen; Wang, Xizhao; Luo, Xi; Zhong, Yu (Frontiers in Sustainable Food Systems, 2025)
Counties are key regions for grain production in China, and it is essential to incentivize county governments to focus on grain production to ensure national food security. This study uses county-level data from 2000 to 2021 to assess the impact of the reward policy for major grain-producing counties (RPMGC) on county governments' incentives to support grain production (CGISGP), employing a difference-in-differences approach. The results show that: (1) The implementation of RPMGC significantly increased CGISGP, and this result remains robust under parallel trend, placebo, and other robustness tests; (2) Further analysis reveals that the effect appeared in the first year after the policy's implementation and gradually diminished by the fifth year. The policy's impact is not sustained in the long term; (3) The effect was more pronounced in counties with high bonus distribution coefficients, large primary sectors, and significant financial pressure. It is necessary to promptly adjust and improve the RPMGC, accelerate horizontal grain interest compensation mechanisms, and enhance the endogenous motivation of grain-producing counties.